Сервіс для скорочення тексту за допомогою алгоритму обробки тексту textrank - Демченко, А. Є. (ХНУРЕ, 2019)
The goal of this research paper is to create high quality algorithm, that can scrape text of article from third-party sites and summarize it and save sense of the text, but delete all useless with TextRank algorithm.